Strategi Promosi dan Komunikasi Jasa Pendidikan - Cindy, Cindy; Amanda Stevany Nurvita; Mahfud Ifendi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
With increasing competition in the world of education, especially in the era of globalization and digitalization, educational institutions inevitably have to adopt appropriate promotional strategies to attract prospective students. This research aims to find out how to manage communication programs, alternative communication techniques, promotional design, marketing publications and advertising educational services. This research method uses a literature-based approach to analyze promotion and communication strategies for educational services. This research found that an effective communication program will strengthen the reputation of educational institutions and build public trust, combining various communication methods can be a good alternative communication technique, through careful planning, promotional design will be able to attract attention and achieve the marketing goals of educational institutions, publications marketing helps strengthen relationships with prospective students and parents and improves the institution's reputation amidst competition, and overall, advertising educational services is important in increasing the visibility, reputation and attractiveness of the institution amidst increasingly fierce competition. The benefits of this research are expected to be able to increase awareness of institutions in promoting and communicating the services they offer, can become a reference for making strategies, and become an evaluation and improvement for the progress of educational institutions in Indonesia.